PENGARUH MENGUNYAH BUAH NANAS DAN BELIMBING TERHADAP PENURUNAN INDEKS PLAK - Ainul Auliyah A; Rismawati Rismawati; Annisa Suwahru; Natalia Natalia (Poltekkes Kemenkes Bandung, 2026)
Dental and oral health issues remain a major complaint among Indonesians. Lack of awareness and knowledge of the importance of dental and oral health leads to many Indonesians suffering from dental and oral diseases, both children and adults. Caries and periodontal disease are common oral health problems. Dental caries occurs due to the demineralization process resulting from bacterial interactions on the tooth surface. Bacteria are acidic, damaging tooth enamel, leading to dental caries. The primary cause of these diseases is plaque. Healthy teeth can be maintained by consuming fibrous fruits, as the nutrients and fiber contained in these fruits are very good for dental and oral health. Pineapple and star fruit are fruits that contain high levels of water and fiber. In addition, pineapple contains the enzyme bromelain, and star fruit contains epicatechin, which can inhibit or kill caries-causing bacteria, especially Streptococcus mutans, which is commonly found in plaque. This study aims to determine the effect of chewing pineapple and star fruit on reducing plaque index. The type of research used is a literature review. The data collection method used was derived from secondary sources such as journals, books, scientific papers, theses, textbooks, and scientific articles. The research results showed that pineapple and starfruit can reduce plaque index and showed significant results. From the results of this literature review, it can be concluded that chewing pineapple and starfruit can reduce plaque index.